Vibration Control of a Floating Raft System by Synchrophasing of Electrical Machines: An Experimental Study - Yang, Tiejun; Huang, Di; Li, Xinhui; Brennan, Michael J. [UNESP]; Zhou, Liubin; Zhu, Minggang; Liu, Zhigang (ASME International, 2018)
This paper describes an experimental investigation into the vibration control of multiple electrical machines installed on a large-scale floating raft system. Vibration transmission to a flexible hull-like structure that supports the floating raft is controlled by adjusting the phases of the electrical power supply to the machines - a technique known as synchrophasing. Each machine is driven by a phase asynchronous motor and has two counter rotating shafts with adjustable eccentric masses, which allows the dynamic force generated by each machine to be set independently. Up to four rotating machines are considered. A genetic algorithm is used in the search for the optimum relative phases between each machine, because it is impractical to carry out an exhaustive search of the huge number of possible phase combinations. It is demonstrated that vibration control using synchrophasing is feasible in a marine environment, and can achieve significant vibration reduction, by simply adding some sensors and a control system. Reduction in the total transmitted vibration, as measured by the sum of the squared accelerations from 22 error sensors on the hull-like structure, was found to be up to 13 dB, and vibration reduction at higher harmonic frequencies was found to be up to 51 dB.
Keywords: floating raft; hull-like structure; synchrophasing control; vibration isolation